Analysis of Diadochokinesis in Ataxic Dysarthria Using the Motor Speech Profile Program™ - Wang, Yu-Tsai (S. Karger AG, 2009)
AIMS: The Diadochokinetic Rate Analysis (DRA) in the KayPENTAX Motor Speech Profile is a computer program for the analysis of diadochokinesis (DDK). The objective of this study is to evaluate the suitability, reliability, and concurrent validity of the results from the DRA protocol and hand measurement for individuals with ataxic dysarthria, which is characteristically associated with dysdiadochokinesis. METHODS: Twenty-one participants with ataxic dysarthria were recorded as they repeated various syllables as quickly and steadily as possible. The DDK samples were executed by the DRA protocol at different thresholds and were also hand-measured. Analyses were based on the percentage of nonexecutable DDK samples, defined as samples in which the lowest peak intensity during CV syllables is lower than the highest peak intensity during intersyllable pauses, and the comparisons of the results between repeated analyses at different thresholds and between automatic and manual measuring methods. RESULTS: (1) More than one third of the DDK samples were nonexecutable; (2) the reliability at different thresholds and concurrent validity between different measuring methods were both satisfactory, and (3) temporal variation parameters were more inconsistent between different measuring methods than intensity variation parameters. CONCLUSION: DRA has notable limitations in its clinical application but there is a considerable potential for improving its performance.